2016
DOI: 10.1007/s10754-016-9188-2
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing gatekeeping with a revenue scheme for secondary care providers

Abstract: We study implications of a change in the payment scheme for radiology providers in Norway that was implemented in 2008. The change implies reduced fee-for-service and increased fixed budget for a contracted volume of services. A consequence of the change is that private providers have less incentive to conduct examinations beyond the contracted volume. Different from the situation observed before the change in 2008, the volume is no longer determined by the demand side, and a rationing of the supply occurs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Further research is required regarding whether the reduction in total services nationally was due to some of these services being unnecessary (especially in areas where patients had providers close by) or whether people stopped waiting or paying for radiology examinations privately out of pocket [16, 30, 57]. The number of patients using private health insurance increased 12 times from 2006 to 2016, and 30% of such plans were used for specialists and diagnostics [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required regarding whether the reduction in total services nationally was due to some of these services being unnecessary (especially in areas where patients had providers close by) or whether people stopped waiting or paying for radiology examinations privately out of pocket [16, 30, 57]. The number of patients using private health insurance increased 12 times from 2006 to 2016, and 30% of such plans were used for specialists and diagnostics [58].…”
Section: Discussionmentioning
confidence: 99%
“…Visits to a public or private laboratory require a referral from a GP or a specialist to be covered by the National Health Insurance (NHI) [29]. In theory, radiology laboratories can decline to make an appointment, but in practice, this does not happen often because GPs already act as gatekeepers [30].…”
Section: Methodsmentioning
confidence: 99%
“…Paying attention to such mechanisms is crucial when addressing overutilization of imaging. In addition to strategies towards the professionals, more attention should be paid to organizational aspects like, ownership of equipment (Hong et al 2017) and payment scheme (Iversen and Mokienko 2016). Fortunately, the international Choosing Wisely campaign (Levinson et al 2015) together with other measures to reduce overuse have shown that it is possible to address overutilization of radiological services.…”
Section: Potential Solutionsmentioning
confidence: 99%